Assessment Of Diversity For Yield And Its Component Traits In F2 Population Of Wheat (Triticum Aestivum L.) Under Salinity Conditions (Applied Biological Research, 2018)
Genetic diversity analysis of yield and yield contributing traits in F2 population of wheat cross ‘Kharchia 65 x HD 2851’ wasestimated, based on  D2-statistics, for 100 selected phenotypically superior plants that were  grouped into 13 clusters. Clustering pattern revealedthat cluster II and IV  were the largest ones with 14 genotypes. The highest inter-cluster distance  was observed between clusters VII and VIII (11.67), followed by between  clusters VII and X (10.85), VII and IX (9.88) and VII and XII (9.88). This  indicates that plants included in these clusters possess wide genetic diversity.  Further, cluster VIII exhibited high mean value for number of spikelets  spike-1 (18.0), number of grains ear-1 (36.0), grain yield plant-1 (0.911 g) and  biological yield plant-1 (4.342 g). Cluster I showed highest mean value for the  number of grains spikelet-1(3.0), moderate 1000-grain weight (32.95 g) and  acceptable harvest index (34.6%). The clusters VII, I, II, III, XI and XII were  outstanding on the basis of better cluster mean for most of the characters. The genotypes in these clusters should be selected and utilized to the  advanced generation in a breeding program for improved salinity tolerance.
Keywords: Cluster analysis; D2-statistics; genetic diversity; salinity; wheat